Rethinking undergraduate business education : liberal learning for the profession - Colby, Anne, 1946-; Carnegie Foundation for the Advancement of Teaching (San Francisco, CA : Jossey-Bass, 2011)
'This book is from the Carnegie Foundation for the Advancement of Teaching's three-year effort developed in response to concerns about the failures of business education to prepare undergraduates for their responsibilities in society, including in their business practice. Business leaders stress the importance of liberal learning but most liberal arts courses are not well-integrated with the business curriculum. This important resource reports on examples of how the two can be integrated and offers solid recommendations for improvement. The authors also address the value of some perspectives that business can offer to the liberal arts'--
Liberal learning for business education: an integrative vision -- Business and the academy: founding hopes and continuing challenges -- On the ground: the challenges of undergraduate business education -- The meaning and relevance of liberal education -- Teaching for key dimensions of liberal learning -- Pedagogies of liberal learning in business education -- Structural approaches to integration: building institutional intentionality -- Emerging agendas: globalization and entrepreneurship -- The way forward.
'The Carnegie Foundation for the Advancement of Teaching.'--T.p.
Includes bibliographical references (p. 179-184) and index.
Keywords: Business education; Education, Humanistic; Undergraduates